Serum Transforming Growth Factor-Beta 1 Level in Egyptian Systemic Lupus Erythematosus Patients - Manal EL MENYAWI,; Mary FAWZY,; Mohamed HABIB,; Olfat SHAKER, (Archives of Rheumatology, 2018)
Objectives: This study aims to assess the role of transforming growth factor-beta 1 (TGF-β1) in systemic lupus erythematosus (SLE). Patients and methods: The study included 40 female SLE patients (mean age 25.5±6.2 years; range 15 to 39 years) diagnosed according to the American College of Rheumatology criteria and 30 female healthy controls (mean age 26.2±5.9 years; range 16 to 39 years). Disease activity was assessed using SLE Disease Activity Index. Patients were diagnosed with lupus nephritis if they met the criteria for renal disorder. SLE patients and controls were compared in terms of TGF-β1, low and high density lipoprotein, and triglyceride levels. Results: Mean serum TGF-β1 level of patients with SLE was 1385.7±483.1 pg/mL, with a significant difference compared to control group (2079.6±125.4 pg/mL; p<0.001). TGF-β1 was statistically significantly correlated with SLE disease duration. However, there was no statistically significant correlation between TGF-β1 and erythrocyte sedimentation rate, C-reactive protein, 24-hour urinary protein, complement 3, serum cholesterol, low density lipoprotein, or serum triglyceride. TGF-β1 was statistically significantly correlated with discoid rash. There was a statistically significant correlation between SLE Disease Activity Index and serum cholesterol, and triglyceride. Conclusion: Systemic lupus erythematosus patients had lower levels of TGF-β1, without any significant correlation with SLE Disease Activity Index or lipid profile. TGF-β1 had a significant correlation with discoid lupus.